Seasonal patterns and interannual variations of atmospheric circulation over the Bering Sea in 1995–2022 - S. Yu. Glebova (Известия ТИНРО, 2024)
Mean patterns of atmospheric circulation over the Bering Sea in 4 seasons: winter (January-March), spring (April-June), summer (July-September) and autumn (OctoberDecember) are described using the author’s typification of synoptic situations. Frequency of all 6 types of synoptic situations is calculated and the predominant types are determined, by season. Mean values of the meridional and zonal indices of atmospheric circulation and the number and intensity of cyclones in the Bering Sea area are calculated for each season in the period 1995–2022. Cyclonic activity and direction and intensity of general wind transfer, particularly intensity of winter and summer monsoons, are considered separately for the western and eastern parts of the Bering Sea. Interannual variations of all these parameters are traced. For all seasons, the wind transfer over the entire area is determined by cyclonic activity in the western Bering Sea: the higher activity leads to weaker monsoon in winter (northeasterly) and summer (southwesterly) but strengthening in spring (southeasterly) and autumn (northwesterly). Since the middle 1990s, autumns and winters in the Bering Sea became warmer (with the warmest period in the late 2010s when southeasterlies prevailed in winter), but springs became colder (southeastern wind transfer in early 2000s changed to the northeastern one in late 2010s), with no definite tendency for summer, when the meridional index of atmospheric circulation was rather stable and the zonal index had a negative trend (weakening of westerlies). Trends and cycles of oceanographic conditions in the northwestern Bering Sea generally coincided with the changes in wind transfer in any season.